Haqaiq al Hayah al Falastiniyyah fi Syi’ir “Yaumiyyat Jarh Falistin” li Mahmoud Darwish - Nushrotun Nida (Arabic Language and Letters Department, 2021)
Talking about Mahmud Darwis works is as if we were invited to see the real world reality. In this study, the researcher used the object of Mahmud Darwis' poetry entitled